Recent Advances Toward Robust N-Protecting Groups for Glucosamine as Required for Glycosylation Strategies - Aly, Mohamed Ramadan El Sayed; El Ashry, El Sayed H (Advances in carbohydrate chemistry and biochemistry, 2016)
2-Amino-2-deoxy-d-glucose (d-glucosamine) is among the most abundant monosaccharides found in natural products. This constituent, recognized for its ubiquity, is presented in most instances as its N-acetyl derivative 2-acetamido-2-deoxy-d-glucopyranose (N-acetylglucosamine, GlcNAc, NAG). It occurs as the β-linked pyranosyl group in polysaccharides and oligosaccharides, and sometimes as the monosaccharide itself, either in its native state or as a glycoconjugate. The compound's acylation profile and other aspects of its structure are important elements in determining the variety of reactivities and functions of the molecule as a whole. Methods elaborated to investigate these challenges have been intensively reviewed; however, a relatively more comprehensive reviewing of this subject is introduced here to cover some aspects that have not been sufficiently covered. This might enable those who are beginners in this field to be aware of the subject in a more comprehensive context. 2-Amino-2-deoxy-d-glucosylation strategies demand robust amino-protecting groups that survive under a variety of chemical conditions, yet provide groups that can be deprotected under relatively mild conditions. At the end of this review, a table that includes all the N-protecting groups that have been used for glucosamine is provided to introduce them at a glance to aid in constructing building blocks that will act as useful 2-amino-2-deoxy-d-glucosyl donors.